Problematika Pendidikan Anak Di Keluarga Muslim Buruh Pabrik: (Studi Kasus Keluarga Pekerja Pabrik Rokok Diva Sejahtera Sidoarjo) - M. Badrul Huda el Haque (AT-THUFULY : Jurnal Pendidikan Islam Anak Usia Dini, 2021)
Abstract:. Religious education in children is first obtained from the family environment and the main component is parents. The presence of parents in raising children is one thing that cannot be underestimated and ordinary. The absence of parents in the family will result in children being "orphaned" even for reasons of working and earning a living. The research is descriptive qualitative with the research strategy used is a case study, data analysis is carried out through qualitative analysis. Sources of research data (1) informants or resource persons consisting of the ranks of company owners, administrative staff, human resources, marketing, foremen and wholesale employees at PR. Diva Sejahtera Sidoarjo. (2) observation, by examining the object of research in the form of companies and their activities and the villages they live in and their religious activities there. (3) Archives and documents in PR. Diva Sejahtera in the form of everything that can be used as a reference by researcher. The results of this study indicate: (1) the complexity of the problems of workers, from economic, socio-cultural problems to the problems of their children's education. (2) the problems that arise stem from economic, social and cultural problems that entangle their lives. (3). Educational problems faced cannot be separated from educational factors. In this study, it was concluded that it needed full awareness of workers about the importance of education, especially Islamic education.